CURRICULUM MANAGEMENT IN ENHANCING THE QUALITY OF EDUCATION IN THE PACKAGE C EQUIVALENCY PROGRAM AT PKBM SEROJA - Perestian Ares Sandi; Saliman; Riko Septiantoko (SOSIOEDUKASI, 2025)
Curriculum management serves as a key factor in improving the quality of education in the Package C Program, which provides alternative learning opportunities for individuals outside the formal education system. This study aims to analyze the practices of curriculum planning, implementation, and evaluation to enhance the quality of non-formal education. Using a descriptive qualitative approach with a multi-site design, this research examines curriculum management in improving educational quality within the Package C Equivalency Education Program at PKBM Seroja, Riau. Respondents were selected purposively, consisting of the head of the institution, teachers, curriculum staff, and students. Data were collected through in-depth interviews, participatory observations, and document analysis of official school records. Data analysis followed the model of Miles et al. (2014), including data reduction, data display, and conclusion drawing. The findings reveal that curriculum management at PKBM Seroja has been carried out adaptively through participatory planning, flexible organization, andragogical learning approaches, and project-based evaluation. However, several challenges persist, such as limited tutor competence, inadequate facilities, and insufficient operational funding. Quality improvement strategies include tutor training, external partnerships, learning digitalization, and the enhancement of authentic assessments. This study concludes that the success of curriculum management in non-formal education depends on collaboration, innovation, and the institution’s ability to adapt to the diverse needs of adult learners.